Introduction Of Post-Harvest Processing Tehcnology To Increase Production Capacity And Quality Of Coffee Processed By Uph Sekar Rindu, Dampit, Malang Regency - Wenny Bekti Sunarharum; Sudarminto Setyo Yuwono; Erni Sofia Murtini; Kiki Fibrianto; Elok Waziiroh; Eka Shinta Wulandari; Laila Yum Wahibah (Journal of Innovation and Applied Technology, 2018)
Besides coffee productivity, the most prominent problem in the coffee production is related to the consistency of quality. This community service program is specifically aimed to resolved coffee quality and productivity problems encountered by Sridonoretno coffee processing and producing unit in UPH Sekar Rindu. The approach in addressing those problems includes four steps. First step is the community empowerment through training on coffee quality and introduction on selective picking/harvesting method. Secondly, writing and documenting standard operating procedures for harvesting, for some common coffee post harvest processing methods as well as an appropriate storage procedure that could be applied by the community. Thirdly, the introduction of machinery including coffee huller and scale to improve coffee productivity. The last effort is to perform certification and grading of the quality of Sridonoretno green coffee beans.